Establishing zebrafish nutritional requirements in phospholipids, minerals and vitamins: effects on growth and skeletal development - Martins, Gil Sales Marques (2017)
Dissertação de mesrado, Aquacultura e Pescas, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2013